Hubungan Pengetahuan Diet Jantung Dengan Kepuasan Pasien Rawat Inap Kelas III Di RSUD Surakarta - Eka Pratiwi, Mega, Luluk Ria Rakhma S.Gz., M.Gizi, Ririn Yulianti, S.Si.T., M.Si (2016)
Good knowledge of nutrition is a very important factor in determining person's attitude and behavior toward food. Hospitalized heart disease patients who have a good knowledge about heart disease diet will finish food that provided by hospital. One of the efforts of hospital nutrition services in order to achieve optimal nutritional status through the provision of heart disease diet for heart patients. This aims to provide an appropriate diet therapy related to the patient's condition to accelerate the healing process. Characteristics of heart disease diet is enough energy, enough protein, moderate fat and low salt thus affecting the taste. Patients' satisfaction of the food sevice can be identified by food waste. In fact, patients still complaint about the soft food that is served in the hospital. The purpose of this study was to determine the relationship between knowledge of heart disease diet and hospital patients satisfaction at class III Surakarta hospital. This type of research was observational with cross sectional design. Subjects were 31 patients who received heart disease diet class III in the form of soft or puree food. Subjects were obtained through consequtive sampling. Knowledge of heart disease diet was obtained through questionnaires and patients satisfaction obtained through Comstock plate waste form. Analysis of the data in this study using Spearman Ranks test. The level of knowledge of most of the subject was less knowledge 80%. Most of food waste was staple food or puree vegetables wich amounted for 77% and 83.9% respectively. The results of bivariate test showed that knowledge of heart disease diet related with meal porridge waste (p = 0.002) and vegetables waste (p = 0:03) and there was no relation between knowledge of heart disease diet and animal protein waste (p = 0.54), plant protein waste (p = 0.25), fruit waste (p = 0.21) and snacks waste (p = 0.94) There was a relationship between knowledge of heart disease diet and porridge and vegetables waste and there was no relation between knowledge of heart disease diet and animals and plant protein waste, fruit waste, and snacks waste.